Compound common-path digital holographic microscope - Qu, Weijuan (2013)
Digital holographic microscopy provides 3D quantitative phase imaging that is suitable for high resolving investigations on reflective surfaces as well as for transmissive materials. An optical configuration for a digital holographic microscope and a method for digital holographic microscopy are presented. A cube beam splitter in the optical path, with a small angle between the optical axis and its central semi-reflecting layer, both split and combine a diverging spherical wavefront emerging from a microscope objective to give off-axis digital holograms. Since the object wave and the reference wave go the same way to the CCD camera, it is called common-path digital holographic microscopy. When a plane numerical reference wavefront is used for the reconstruction of the recorded digital hologram, the phase curvature introduced by the microscope objective together with the illuminating wave to the object wave can be physically compensated. A compound digital holographic microscope (with reflection mode and transmission mode) has been build up based on this unique feature. Results from surfaces structures on silicon wafer and micro-optics on fused silica demonstrate applications of this compound digital holographic microscope for technical inspection in material science.